PSAK 72: EVALUASI PENERAPAN AKUNTANSI PADA PERUSAHAAN PENGEMBANG REAL ESTATE DI BATAM - Widda Royanisa Manalu; Alfonsa Dian Sumarna (Jurnal Bisnis Terapan, 2023)
The PSAK 72 regarding Contract Revenue from Customers effective as of 2020, which replaces some of the old rules, has focused on the migration of revenue recognition at PT. RPM is one of the real estate development companies on Batam Island. This comparative quantitative descriptive research aims to analyze the differences in revenue recognition reported by companies when implementing and not implementing PSAK 72. Data collection uses interview methods and documentation related to income transactions for the period October to December 2020. This research found that the 2020 reporting of PT. RPM still uses the old rules. There are seven types of income for PT. RPM are fine revenue, first-party fee revenue, cancellation revenue, other revenue, rent revenue, waarmerking revenue, and giro service revenue. The types of revenue that are not included in the PSAK 72 standard are other revenue, rent revenue, and giro service revenue. PSAK 72 set that revenue can be recognized when the performance obligation has been fulfilled or the transaction in the form of a contract has been completed. All transactions related to contract revenue in October-December 2020 have been fulfilled or the performance obligations to customers have been completed. The analysis of the calculation of total revenue if implementing PSAK 72 and not implementing PSAK 72 is the same as the amount reported in 2020.